1986
DOI: 10.1007/bf00428643
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic susceptibility of clinical isolates of Pseudomonas aeruginosa

Abstract: Three hundred and twenty two clinical isolates of Pseudomonas aeruginosa collected in Morelia, México, were analyzed for in vitro susceptibility to five antibiotics by agar dilution tests. Antibiotic resistance was shown by 50% of total isolates. Frequencies of resistance were: streptomycin, 47%; gentamicin, 13%; tobramycin, 8%; and carbenicillin, 7%; no amikacin resistance was found. The more common resistance patterns were streptomycin, gentamicin-streptomycin, and tobramycin-gentamicin-streptomycin. Resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

1987
1987
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
4
0
1
Order By: Relevance
“…Such resistance-modifying activity of the silver becomes quite important given P. aeruginosa is known rarely to be susceptible to augmentin [ 53 ], and augmentin resistance is quite prevalent among its clinical isolates [ 54 ]. Streptomycin-resistance was reported by [ 55 ] to be among the most common resistance patterns in P. aeruginosa clinical isolated from Mexico.…”
Section: Resultsmentioning
confidence: 99%
“…Such resistance-modifying activity of the silver becomes quite important given P. aeruginosa is known rarely to be susceptible to augmentin [ 53 ], and augmentin resistance is quite prevalent among its clinical isolates [ 54 ]. Streptomycin-resistance was reported by [ 55 ] to be among the most common resistance patterns in P. aeruginosa clinical isolated from Mexico.…”
Section: Resultsmentioning
confidence: 99%
“…B14-6 was susceptible to gentamicin (MIC 0.5 µg/mL), tobramycin (MIC 0.5 µg/mL), kanamycin (MIC 2 µg/mL), and apramycin (MIC 4 µg/mL) at 25 °C. However, this bacterium was resistant to streptomycin (MIC 32 µg/mL), which was comparable to the mesophilic Pseudomonas aeruginosa , often displays resistance to streptomycin ( Table 1 ) [ 21 , 22 ]. Taken together, these results indicate that Pseudomonas sp.…”
Section: Resultsmentioning
confidence: 99%
“…However researchers have demonstrated the bactericidal activity of streptomycin against Pseudomonas aeroginosa [19] [28] but recent studies has demonstrated the developing streptomycin resistance in Pseudomonas aeruginosa [29] [30].…”
Section: Discussionmentioning
confidence: 99%